Determination of Knowledge of Patients Regarding Psoriasis - Maria Khalid; Rabia Ishfaq; Sana Younas; Komal Shehzade; Hasan Khalid; Qurat ul Ain Zulfi (Journal of University Medical & Dental College, 2024)
ABSTRACT BACKGROUND & OBJECTIVE: Psoriasis, a chronic, non-communicable skin condition, significantly impacts patients’ quality of life. This study aimed to assess the knowledge levels among psoriasis patients, categorized into adequate, moderately adequate, and inadequate, to identify educational needs and opportunities for improved patient education. METHODOLOGY: This cross-sectional study was conducted at the Department of Dermatology, Imran Idrees Hospital, affiliated with Sialkot Medical College, from October 2023 to February 2024. It involved 218 patients aged 16-60 years, diagnosed with psoriasis for over a year. Knowledge levels were assessed using a self-administered questionnaire, with scores ≥7 out of 10 considered adequate knowledge. RESULTS: Out of the participants, 57.8% had inadequate knowledge about psoriasis, 32.6% had moderately adequate knowledge, and only 9.6% had adequate knowledge. The analysis showed no significant differences in knowledge levels across age, gender, duration of disease, education, and economic status (p-value > 0.05). CONCLUSION: The study revealed a significant gap in the knowledge about psoriasis among patients, emphasizing the obligation for routine patient education and counseling. This approach could improve treatment adherence and outcomes, reducing misconceptions and treatment discontinuation.